Legal Assistance for Underprivileged Communities to Access Justice within the Human Rights Perspective - Ikbal, Ikbal; Datuan, Gabriella Almasari (Faculty of Law Universitas Lampung, 2023)
Legal aid promotes justice and human rights, which the central and local governments should provide. Unfortunately, the provision of legal aid for underprivileged communities still requires improvement. Legal aid provided by legal aid activists, institutions, mass organizations, political parties, and non-governmental organizations is still not optimal due to administrative problems and the legalization of legal aid practices. This research provides insights into the significant benefits of legal assistance for underprivileged communities. This research also proposed a novel legal perspective and reform regarding equal distribution of justice.